High Red Cell Distribution Width and Low Absolute Lymphocyte Count Associate With Subsequent Mortality in HCV Infection - Sofi Damjanovska; Perica Davitkov; Surya Gopal; Lenche Kostadinova; Corrine Kowal; Alyssa Lange; Anita Moreland; Carey Shive; Brigid Wilson; Taissa Bej; Sadeer Al-Kindi; Yngve Falck-Ytter; et al. (Case Western Reserve University, 2021)
Background: Hepatitis-C virus (HCV) chronic infection can lead to cirrhosis, hepatocellular carcinoma (HCC), end-stage liver disease, cardiovascular disease (CVD), and mortality. Transient Elastography (TE) is used to non-invasively assess fibrosis. Whether immune monitoring provides additive prognostic value is not established. Increased red-cell distribution width (RDW) and decreased absolute lymphocyte count (ALC) predict mortality in those without liver disease. Whether these relationships remain during HCV infection is unknown.  Materials and Methods: A retrospective cohort of 1,715 single-site VA Liver Clinic patients receiving Transient Elastography (TE) 2014-2019 to evaluate HCV-associated liver damage were evaluated for RDW and ALC in relation to traditional parameters of cardiovascular risk, liver health, development of HCC, and mortality. Results: The cohort was 97% male, 55% African American, 26% with diabetes mellitus, 67% with hypertension, and 66% with tobacco use. After TE, 3% were subsequently diagnosed with HCC, and 12% (n=208) died. Most deaths (n=189) were due to non-liver causes. The TE score associated with prevalent CVD positively correlated with atherosclerotic cardiovascular disease (ASCVD) 10-Year Risk Score, age, RDW, and negatively correlated with ALC. Patients with anisocytosis (RDW above 14%) or lymphopenia (ALC level under 1.2x109/L) had greater subsequent all-cause mortality, even after adjusting for age, TE score, and comorbidities. TE score, and to a modest degree RDW, were associated with subsequent liver-associated mortality, while TE score, RDW, and ALC were each independently associated with non-liver cause of death. Conclusion: Widely available mortality calculators generally require multiple pieces of clinical information. RDW and ALC, parameters collected on a single laboratory test that is commonly performed, prior to HCV therapy may be pragmatic markers of long-term risk of mortality.